Canonisation as Innovation Anchoring Cultural Formation in the First Millennium BCE - Agut-Labordère, Damien; Versluys, Miguel John (Brill, 2022)
Canonisation is fundamental to the sustainability of cultures. This volume is meant as a (theoretical) exploration of the process, taking Eurasian societies from roughly the first millennium BCE (Babylonian, Assyrian, Persian, Greek, Egyptian, Jewish and Roman) as case studies. It focuses on canonisation as a form of cultural formation, asking why and how canonisation works in this particular way and explaining the importance of the first millennium BCE for these question and vice versa. As a result of this focus, notions like anchoring, cultural memory, embedding and innovation play an important role throughout the book.